Mencari Murray Bookchin dalam Belantara Ilmu Sosial - Putra, Moch. Rizky Pratama (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2021)
This study discusses the metatheory of sociological paradigms as a method for finding and placing Murray Bookchin's concept of thinking based on the foundations of his thought, namely dialectical naturalism as philosophical basis and the concept of social ecology as praxis. This study uses library research approach, namely a comparative study to explore and discover Murray Bookchin's social ecology concepts in intersection with the sociological paradigm typology George Ritzer, Margaret Poloma, Gibson Burrel, and Gareth Morgan. Murray Bookchin, connect the social facts paradigm and social definitions in social science. Here lies the importance of the exemplar concept developed by Ritzer. First, the position of humans who are attached or deterministic due to the confinement of hierarchical social institutions causes them to accept the